Expand the constricted-review article - Shetty, Sharath Kumar; Vigneshwaran A, Roginth; Kumar Y, Mahesh; Madhur, Vijayananda (International Journal of Dental Research, 2017)
A combination of orthopaedic and orthodontic tooth movements are required for expansion of palate to correct maxillary transverse discrepancy. Expansion of the palate can be achieved by three different treatment methods mainly Rapid maxillary expansion, slow maxillary expansion and surgically assisted maxillary expansion. Among the different methods rapid maxillary expansion brings about significant changes in the dental transverse measurements (Agarwal A, Mathur R International journal of clinical pediatric dentistry 2010). This article aims to review the various appliances used for maxillary expansion.